Ocular Surface Disease and Dry Eye Severity in Glaucoma Patients at Urban Private Eye Care Centres in Malaysia - Gan EH; Woo WW; Seng KF; Singh P; Lee MY; Kong VY; Khoo SP; Lee MW; Liang LK (Clinical Ophthalmology)
Eng Hui Gan,1 Wen Wei Woo,1 Kheong Fang Seng,1 Pall Singh,2 Ming Yueh Lee,3 Vui Yin Kong,4 Say Peng Khoo,4 Mun Wai Lee,5 Liau Kok Liang6 1International Specialist Eye Centre, Kuala Lumpur, Selangor, Malaysia; 2Tun Hussein Onn National Eye Hospital, Petaling Jaya, Selangor, Malaysia; 3Parkcity Medical Centre, Kuala Lumpur, Selangor, Malaysia; 4Synergy Specialist Eye Centre, Kota Kinabalu, Sabah, Malaysia; 5LEC Eye Centre, Ipoh, Perak, Malaysia; 6Mahkota Medical Centre, Melaka, MalaysiaCorrespondence: Eng Hui Gan, International Specialist Eye Centre (ISEC) Kuala Lumpur, Level 8 Centrepoint South MidValley City, Kuala Lumpur, 59200, Malaysia, Tel +603 2284 8989, Fax +603 2284 4330, Email ganenghui@yahoo.com.myBackground: Ocular surface disease (OSD) severity varies among glaucoma patients and is exacerbated by intraocular pressure (IOP)-lowering medications.Purpose: To determine OSD prevalence and dry eye severity among glaucoma patients at nine private clinics in Malaysia.Methods: This multicentre, cross-sectional observational study recruited glaucoma patients undergoing routine eye examinations, with IOP ≤ 21mmHg receiving anti-glaucoma eye drops. OSD was assessed through National Eye Institute (NEI) scoring, tear film break-up time (TBUT), hyperaemia grading, Schirmer’s tests and questionnaires on symptom evaluation, OSD index and quality of life (QoL).Results: Our cohort (n = 406, mostly male, ethnically Chinese, mean 63.5 ± 11.5 years, mean IOP 15.34 ± 2.95mmHg) frequently used prostaglandin analogues or PGA/beta-blockers and had cornea total NEI scores of 3.64 ± 2.76, mostly with minimal (51.2%) or mild (40.4%) epitheliopathy. Mean TBUT was 6.59 ± 3.08s (25.0%) in patients with severe lipid deficiency dry eye (DE). Bulbar conjunctiva hyperemia (70.4%) and palpebral conjunctiva hyperemia (68.0%) were mild. Schirmer’s test showed that most had tear deficiency (70.2%) with severe DE (38.9%). Questionnaires reported ocular symptoms in few patients, but 69.2% had DE symptoms (13.1% moderate/severe). While QoL was good, several patients had QoL and OSD index scores suggesting some adaptation to ocular symptoms and discomfort, with most patients being unconcerned (43– 60%) by the occurrence of eye drop side effects (75.4%).Conclusion: Normal-mild DE or OSD can be asymptomatic, and the symptoms are unlikely to bother most patients. However, as OSD severity varies in patients with glaucoma, it should be evaluated using questionnaires and clinical tests to ensure that subjectively asymptomatic individuals are not missed.Keywords: glaucoma, ocular surface disease, prevalence, questionnaires, clinical tests